Model Pengembangan Kewirausahaan Berbasis Inovasi di Kota Jambi - Novi Peramasari; Ermaini Ermaini (J-MAS (Jurnal Manajemen dan Sains), 2026)
Entrepreneurship is a crucial factor in regional economic development. Micro, Small, and Medium Enterprises (MSMEs) in Jambi City possess significant potential; however, they still face limitations, particularly in terms of innovation capacity. In the digital era, innovation has become a key driver in enhancing business competitiveness and sustainability. The main challenges encountered include the low capacity of human resources, limited access to technology, and a weak supporting ecosystem. These constraints hinder MSMEs from optimizing their performance and adapting to rapidly changing market dynamics. Therefore, this study aims to develop an innovation-based entrepreneurship model that can effectively improve the performance of MSMEs.